RISK-BASED ASSESSMENT ON MALAYSIA’S OFFSHORE JACKET PLATFORM - Narayanan,, S.P (2012)
Malaysia has approximately 200 fixed offshore structures, some of which have been in operation for over 40 years, which is well beyond its design life. In order for these ageing fixed structures to continue in service or extend its operation, their current structural integrity condition needs to be identified, addressed, prioritized and appropriate mitigation measures should be implemented. The aim of the research was to modify the framework for Structural Integrity Management developed by AMOCO for carrying out risk based assessment of Malaysia’s fixed offshore platforms. This required acquiring actual fixed offshore structure data, which comprises of design, assessment and inspection records. Two important components of this framework were identified as 1) Base line Risk ranking of Malaysia’s offshore platforms and 2) Development of a Risk Based Underwater Inspection (RBUI) programme. The classification of the platforms showed that many of the structures have exceeded the design life of 30 years. The baseline risk evaluation of the 186 platforms showed that fifty five platforms were in “very high risk” category. A risk based underwater inspection guideline was also developed. A case study was done to illustrate how it affects the inspection planning of the offshore structures.